Desenvolvimento de um equipamento portátil para análise de sementes utilizando a técnica do biospeckle laser - Gomes, José Eduardo Silva (2022)
In modern agriculture, the high competitiveness of the market requires greater control of seed quality and, to meet this demand, several technologies have been developed in order to determine the vigor and viability of seeds. In this context, the Biospeckle Laser technique, based on the use of laser and optics, presents itself as an alternative with great potential, as it allows non-destructive analyses, the elimination of subjectivity and the reduction of time and costs. Biospeckle Laser (BSL) analyses are performed using an experimental arrangement consisting of a laser emitter, optical devices, a video camera and a computer that processes the analyses using statistical and mathematical treatments. Due to the physical dimensions of these equipment and accessories, traditional setups occupy a space of the order of 0.25 m2 a 2 m2. In addition, this is a technique that is very sensitive to external interferences such as vibrations and other forms of lighting. These characteristics make that BSL analyses are limited to laboratories and have hindered their intensive use. Commercially, there are still no tools to perform seed analysis using the biospeckle technique and, therefore, this technology is not yet available at production sites and in seed analysis laboratories. Based on this observation, this study was carried out in order to investigate the feasibility of building a compact and portable equipment dedicated to the analysis of seed quality and vigor using the biospeckle laser technique. Thus, the experiments performed demonstrated that factors such as the stability of the laser power supply, external lighting and mechanical vibrations interfere in BSL analyses. In conclusion, the developed prototype presented technical features and solutions that made it possible to carry out these analyses outside the research labs at universities, in addition to pointing out perspectives for future works.